INTERNATIONAL LAW OF SMUGGLING - Noor Rashid Mir Akmam; Siti Nursyakirah Yuslan (UNISSULA, 2019)
Smuggling is the act of carrying goods or people illegally and hidden, like out of a building, into jail, or through of border, Contrary to the law or other regulations. Smuggling encouraged various reasons. These include illegal trade, such as drugs, Immigration and illegal migration, avoid excise, Smuggling of illegal goods to prisoners, or smuggling stolen goods. Another example is the financial motive for it is not like bringing banned items past a security checkpoint (as in airfield) or removal of confidential documents from the state or government officials. Type the smuggling of goods, people and wild creatures.